Tobacco smoking as a risk factor for tuberculous pleural effusion: a case-control study. (2020) - Tewatia, Pavit; Kaushik, Rajeev Mohan; Kaushik, Reshma; Kumar, Sanjeev
Abstract: This study assessed the tobacco smoking-associated risk for tuberculous pleural effusion (TPE) in India. Ninety-two patients with TPE and 184 controls were randomly selected and assessed regarding their tobacco-smoking status and type, quantity and duration of tobacco used. Odds ratios (ORs) for the association of smoking cigarette, beedi and cigarette or beedi with TPE were 19.22 ( p < 0.0001), 2.89 ( p = 0.0006) and 4.57 ( p < 0.0001) respectively. ORs for developing TPE increased with an increase in beedi/cigarette consumption, duration and pack years of smoking ( p < 0.001 each). TPE was significantly associated with confounding risk factors viz., regular alcohol use (OR = 1.89, p = 0.019), history of contact with tuberculosis (TB) patient (OR = 8.07, p < 0.0001), past history of TB (OR = 22.31, p < 0.0001), family history of TB (OR = 9.05, p = 0.0002) and underweight (OR = 3.73, p = 0.0009). Smoking (OR = 3.07, p < 0.001), regular alcohol use (OR = 2.10, p = 0.018), history of contact with TB patient (OR = 4.01, p = 0.040), family history of TB (OR = 10.80, p = 0.001) and underweight (OR = 5.04, p < 0.001) were independently associated with TPE. Thus, both cigarette- and beedi-smoking have a significant association with TPE. The risk for TPE in tobacco smokers is dose- and duration-dependent.